The psychological foundation of education and its influence on learning according to experts - Ihwan Mahmudi; Nur Reformawati; Amirah Mahmud Abdullah (Journal of Counseling, Education and Society, 2024)
Educational Psychology is one of the branches of psychological science that focuses on studying about how to understand teaching and learning in an educational environment. There is also an explanation that the psychology of education is a science and applied science that outlines various human activities in relation to the educational situation. One example is learning how to attract students' attention so that they are more receptive to the lessons taught. From the explanation above, it can be taken that psychology in the field of education is intended to influence educational activities so that the learning and teaching and learning process can take place more effectively by paying attention to the psychological response and behavior of students. As with the study of other sciences, educational psychology has limitations in terms of what is discussed in it. Basically, educational psychology studies several things such as the environment and heredity of education, the development and mental health of students, learning processes and evaluations and others.